2008
DOI: 10.1139/g08-043
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA amount and genome downsizing in natural and synthetic allopolyploids of the generaAegilopsandTriticum

Abstract: Recent molecular studies in the genera Aegilops and Triticum showed that allopolyploidization (interspecific or intergeneric hybridization followed by chromosome doubling) generated rapid elimination of low-copy or high-copy, non-coding and coding DNA sequences. The aims of this work were to determine the amount of nuclear DNA in allopolyploid species of the group and to see to what extent elimination of DNA sequences affected genome size. Nuclear DNA amount was determined by the flow cytometry method in 27 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 53 publications
5
60
5
4
Order By: Relevance
“…exhibit a similar loss, indicating that DNA elimination occurs soon after allopolyploidization (Nishikawa and Furuta 1969;Furuta et al 1974;Eilam et al 2008Eilam et al , 2010. Also, the narrow intraspecific variation in DNA content of the allopolyploids supports that the loss of DNA occurred immediately after the allopolyploid formation and that there was almost no subsequent change in DNA content during the allopolyploid species evolution (Eilam et al 2008).…”
Section: Cytological Diploidizationmentioning
confidence: 65%
See 2 more Smart Citations
“…exhibit a similar loss, indicating that DNA elimination occurs soon after allopolyploidization (Nishikawa and Furuta 1969;Furuta et al 1974;Eilam et al 2008Eilam et al , 2010. Also, the narrow intraspecific variation in DNA content of the allopolyploids supports that the loss of DNA occurred immediately after the allopolyploid formation and that there was almost no subsequent change in DNA content during the allopolyploid species evolution (Eilam et al 2008).…”
Section: Cytological Diploidizationmentioning
confidence: 65%
“…Also, the narrow intraspecific variation in DNA content of the allopolyploids supports that the loss of DNA occurred immediately after the allopolyploid formation and that there was almost no subsequent change in DNA content during the allopolyploid species evolution (Eilam et al 2008). In triticale (a synthetic allopolyploid between wheat and rye, Secale cereale), Boyko et al (1984Boyko et al ( , 1988 and Ma and Gustafson (2005) found that there was a major reduction in DNA content in the course of triticale formation, amounting to 9% for the octoploid and 28-30% for the hexaploid triticale.…”
Section: Cytological Diploidizationmentioning
confidence: 67%
See 1 more Smart Citation
“…All diploids mulberry species studied in this report are potential parents for crossbreeding. allopolyploids of several Triticeae species, nuclear DNA amounts are significantly smaller than the sum of their parental species (Eilam et al 2008(Eilam et al , 2009). Leitch & Bennett (2004) identified a tendency for 1Cx values of higher ploidy species to be smaller; however, in mulberry, the 1Cx values of three of four hexaploids were larger than those of diploids, although the 1Cx values of the docosaploid and a hexaploid were smaller and slightly smaller, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an increase in repetitive sequences may lead to an increase in genome size, whereas after polyploidization genome size can be rapidly reduced within one generation (Eilam et al 2008(Eilam et al , 2009). Both events may lead to changes in the 2C DNA value (the unreplicated genome DNA content).…”
Section: And Oshigane 1960)mentioning
confidence: 99%